Touria Khannous. African Pasts, Presents, and Futures. Generational Shifts in African Women’s Literature, Film, and Internet Discourse. Lanham: Lexington, 2013. xxv + 203 pp. - Marzia Caporale (Studies in 20th & 21st Century Literature, 2015)
Review of Touria Khannous. African Pasts, Presents, and Futures. Generational Shifts in African Women’s Literature, Film, and Internet Discourse. Lanham: Lexington, 2013. xxv + 203 pp.
Keywords: Touria Khannous; Africa; Francophone; literature; film; feminism